Rubio Angulo, J. (2015). Hacia una hermenéutica de nuestra conciencia histórica. Bogotá: Editorial Pontificia Universidad Javeriana. Colección Anábasis. ISBN: 978-958-716-874-7. Número de páginas: 142. - Editor, El; Pontificia Universidad Javeriana (2016)
null